Synergy between Positive Intelligence and Critical Thinking: A Study in Educational Psychology Master’s Students in the San Martin Region, Peru - Mabel , Contreras-Julian Rosa; Manuel , Delgado-Bardales Jose; Keller , Sanchez-Davila; Pilar , Palomino-Alvarado Gabriela del (Journal of Ecohumanism, 2024)
The aim of the study was to determine the relationship between positive intelligence and critical thinking in the Master’s students of Educational Psychology at the Cesar Vallejo University of Tarapoto. A basic methodology was used, with a quantitative approach, non-experimental design and descriptive correlational scope. A population and sample of 80 students was counted. The results showed that positive intelligence is at a medium level with 95% and critical thinking is also medium with 84%. It was concluded that there is a very low, non-significant positive relationship between positive intelligence and critical thinking in the Master’s students of Educational Psychology, with a statistical coefficient of Spearman’s Rho of 0.151 and a p-value of 0.181. In addition, there is only 2.28% of variability.